Self Efficacy towards Academic Procrastination in Physics Subjects Assisted by Google Sites for High School Students - Trikusyanti, Rita Nunung (International Journal of Active Learning, 2022)
The study was conducted to determine the level of self-efficacy, academic procrastination. Identify the relationship between self-efficacy and academic procrastination in physics subjects assisted by google sites during the pandemic. The research subjects were 113 students, XI MIPA and XII MIPA at SMA Negeri 1 Tempel Sleman. The data collection instrument used a self-efficacy scale and a procrastination scale. The self-efficacy scale has a Cronbach alpha reliability coefficient of 0.919, and the academic procrastination scale has a Cronbach alpha reliability coefficient of 0.955. The p-value for the self-efficacy variable with the theoretical procrastination variable is 0.2000.05. It can be concluded that the self-efficacy variable with the academic procrastination variable has the data distribution following a normal distribution. The results of the linearity test show that the value of sig. Deviation from linearity is 0.937 0.05, so it can be concluded that the two variables have a linear relationship. Based on the calculated r-value (Pearson correlation) 0.836, the r table with the number of subjects N = 113 is 0.195. It can be concluded that 0.836 0.195, then there is a correlation between the self-efficacy and academic procrastination variables. If self-efficacy is high, then academic procrastination is low. The perpetrators of academic procrastination were 10.6% of the entire sample of students. Influence of self-efficacy of 69.9% on academic procrastination while several other factors influenced 39.1%. The two variables of self-efficacy with academic procrastination have the strength of the relationship, or the degree of the relationship is perfectly correlated